2012
DOI: 10.1002/14651858.cd009517.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial injury in women undergoing assisted reproductive techniques

Abstract: Analysis 1.2. Comparison 1 Endometrial injury between day 7 of the previous cycle and day 7 of the ET cycle vs control, Outcome 2 Live birth or ongoing pregnancy per randomly assigned woman (by embryo transfer history). . . Analysis 1.3. Comparison 1 Endometrial injury between day 7 of the previous cycle and day 7 of the ET cycle vs control, Outcome 3 Miscarriage per clinical pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 16 publications
0
43
0
2
Order By: Relevance
“…We preferentially used live birth, but when this was not reported, we used data reported for ongoing pregnancy, providing this related to viable pregnancy to at least 12 weeks' gestation. Ongoing pregnancy is considered as a primary outcome for effectiveness, and by not including data from these studies, only a partial view of the available evidence would have been represented [10][11][12] .…”
Section: Eligibility Criteriamentioning
confidence: 99%
“…We preferentially used live birth, but when this was not reported, we used data reported for ongoing pregnancy, providing this related to viable pregnancy to at least 12 weeks' gestation. Ongoing pregnancy is considered as a primary outcome for effectiveness, and by not including data from these studies, only a partial view of the available evidence would have been represented [10][11][12] .…”
Section: Eligibility Criteriamentioning
confidence: 99%
“…The latest Cochrane review investigating the effectiveness and safety of endometrial injury performed before embryo transfer in women undergoing ART was published in 2015 [61]. It included a total of 14 trials: thirteen studies comparing endometrial injury performed between day 7 of the previous cycle and day 7 of the embryo transfer (ET) cycle versus no injury, and one study comparing endometrial injury on the day of oocyte retrieval versus no injury.…”
Section: Endometrial Scratching (Injury/biopsy)mentioning
confidence: 99%
“…There was no evidence of an effect on miscarriage, however the evidence is of low-quality. On the contrary, results from the only RCT comparing endometrial injury on the day of oocyte retrieval versus intervention, reported that endometrial injury markedly decreased live birth (RR 0.31, 95% CI 0.14 to 0.69; P value 0.004; 156 women; low quality evidence) and clinical pregnancy (RR 0.36, 95% CI 0.18 to 0.71; P value 0.003; one RCT; 156 women; low-quality evidence), [61].…”
Section: Endometrial Scratching (Injury/biopsy)mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, this beneficial inflammatory effect lasts at least one additional month, thus improving implantation in the subsequent cycle. The exact mechanism of such positive effect on implantation following endometrial sampling, as well as the number of such endometrial stimulations and their timing along the cycle preceding that of embryo transfer, still needs to be determined [67].…”
Section: The Endometriummentioning
confidence: 99%